Sustained small and intermediate size proteins expression in phorbol 12-myristate 13-acetate/ionomycine prolonged stimulated human fibroblasts - Zeinab Abedian; Sadegh Fattahi; Roghayeh Pourbagher; Sahar Edrisi; Amrollah Mostafazadeh (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To compare the protein profile of culture supernatants in stimulated and unstimulated human fibroblasts to find some proteins indicating the presence of fibroblasts and their activation status. Methods: Dermal fibroblasts were stimulated with phorbol 12-myristate 13-acetate (PMA)/ionomycine for 72 h. MTT assay was done to determine cell viability and A/E fluorescent staining was used to evaluate the cell death pattern. Protein analysis was performed by gradient SDS polyacrylamide gel electrophoresis 8%–16%. Results: The supernatant of 24 h cultured both stimulated and unstimulated fibroblasts showed two bands in SDS-PAGE analysis with relative molecular weights of 8.59 and 78.8 kDa. These bands density was decreased during the next 48 h in unstimulated cells while their expression was continued in PMA or PMA/ionomycine stimulated cells and a new 85.3 kDa band was appeared in unstimulated and 72 h PMA stimulated cells. Moreover, we found another seven small size (10–19.5 kDa) proteins in supernatants of 48 h and 72 h unstimulated but not in PMA or PMA/Ionomycine stimulated fibroblasts. Most of these proteins expression were down regulated following fibroblast activation. This down-regulation is consistent with our finding that PMA or PMA/ionomycine stimulated cells exhibited a significant level of apoptosis cell death. Conclusions: Human fibroblasts produce some small to intermediate sized proteins with specific SDS-PAGE profile upon cell activation. Most of these proteins can be excreted in urine and can be immunogen theoretically so this data provided a reliable clue for fibrosis biomarker screening based on designation of an appropriated immunoassay.